Pengaruh Sosial Ekonomi Terhadap Ketimpangan Pendapatan di Provinsi Bali Tahun 2019–2023 - Rasendriya, Cetta; Kenanga, Annisa Bulan; Wahdah, Firosa Aniqotul; Wulandari, Mayva; Gempati, Abel; Rahajeng, Anggi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of IPM, PMA, PDRB, RLS, and population density variables on income distribution inequality in Bali Province. This study employs a quantitative approach, utilizing panel data analysis processed with EViews. The results of this study indicate that HDI has a negative and significant effect, Foreign Direct Investment (FDI) has a positive and significant impact, RLS also shows a positive and significant effect, while GRDP does not show a significant impact on inequality, and Population Density has a positive and significant effect on income distribution inequality in Bali Province. Based on spatial analysis using the hotspot method, the area with high-income distribution inequality based on the Gini Ratio Index data for Bali Province from 2019 to 2023 is Denpasar City.